2014
DOI: 10.3390/atoms2030334
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Kinetic Coupling and Effect of Microfield Rotation on Stark Broadening in Plasmas

Abstract: The study deals with two conceptual problems in the theory of Stark broadening by plasmas. One problem is the assumption of the density matrix diagonality in the calculation of spectral line profiles. This assumption is closely related to the definition of zero wave functions basis within which the density matrix is assumed to be diagonal, and obviously violated under the basis change. A consistent use of density matrix in the theoretical scheme inevitably leads to interdependence of atomic kinetics, describin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(227 reference statements)
0
5
0
Order By: Relevance
“…They concluded that such collisions strongly affect the width and shape of the line profile in the core region where the dynamical effects are included using the frequency-fluctuation-model approach. Demura & Stambulchik (2014) have studied the assumption that the density matrix is diagonal for the calculation of spectral lineshapes and the effect of microfield rotation on Stark profiles. The electron-impact broadening of ion lines has been calculated by Naam et al (2014) using trajectories modified by non-Newtonian mechanics and the Maxwell-Jüttner velocity distribution.…”
Section: Developments In Line Broadening Theorymentioning
confidence: 99%
“…They concluded that such collisions strongly affect the width and shape of the line profile in the core region where the dynamical effects are included using the frequency-fluctuation-model approach. Demura & Stambulchik (2014) have studied the assumption that the density matrix is diagonal for the calculation of spectral lineshapes and the effect of microfield rotation on Stark profiles. The electron-impact broadening of ion lines has been calculated by Naam et al (2014) using trajectories modified by non-Newtonian mechanics and the Maxwell-Jüttner velocity distribution.…”
Section: Developments In Line Broadening Theorymentioning
confidence: 99%
“…Notably, the effects of the directionality of the microfield fluctuations were first researched within the framework of the "standard theory" of the plasma line broadening almost four decades ago, but have largely been forgotten. This approach is recalled and comparisons with computer simulations are made in the paper by Demura and Stambulchik [5].…”
Section: Hydrogen-like Transitionsmentioning
confidence: 99%
“…A plausible answer is that the magnitude and frequency distributions taken separately are insufficient to describe the full dynamics of the plasma fields and, therefore, evolution of the radiator. Indeed, as a result of plasma particle motion, not only does the total field experienced by the radiator change in magnitude, but its direction is varied as well, and these two effects are not independent [5,6]. The different modes of the microfield fluctuations and respective different effects on line broadening were first analyzed based on, and extending, the framework of the 'standard theory' (ST) of plasma line broadening almost four decades ago [7], and recently became a subject of study again [6,8], this time beyond a perturbative approach.…”
Section: Introductionmentioning
confidence: 99%
“…Following [6,8], one introduces 'rotational' and 'vibrational' pseudocomponents of the total microfield F t , ( ) respectively, where n G is a unity vector aligned, for example, along the z-axis. It was shown [6] that the central part of the Lyman-α Stark profile is largely determined by the 'rotational' perturbation. Furthermore, for the range of plasma parameters considered, the linewidth appeared to scale as v N ,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation